TINGLAB TUSHUNISHGA O'RGATISH - Shamsitdinova , Manzura (YANGI DAVR ILM-FANI: INSON UCHUN INNOVATSION G‘OYA VA YECHIMLAR, 2025)
This article highlights the underappreciated role of listening comprehension in English language teaching. It analyzes the traditional focus on repetitive drills and imitation that often fail to expose learners to authentic spoken English. The article proposes a systematic, learner-centered approach to prioritize listening at beginner and intermediate levels. Strategies include storytelling, use of gestures, minimal translation, listening at natural speed, and a variety of comprehension activities. These techniques aim to enhance real understanding of spoken language and support the transition from listening to speaking. The article concludes by emphasizing the importance of structured, authentic listening tasks to build stronger communicative competence in English learners